2016
DOI: 10.33736/jaspe.309.2016
|View full text |Cite
|
Sign up to set email alerts
|

Poisson and Negative Binomial Regression Models Application to Model the Factors of Car Ownership in Akure, South West, Nigeria

Abstract: Increase in number of cars without commensurate increase in the number of transport facilities and infrastructures has led to diverse traffic problems in many Nigerian cities like Akure. Factors which contribute to increase in the numbers of cars owned in Akure metropolis were investigated in this study. The study area was divided into three density zones namely High, Medium and Low while, data was collected using well-structured household questionnaire survey distributed amongst residents; with the survey yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 7 publications
(8 reference statements)
2
5
0
Order By: Relevance
“…To further test the effect of school location on the relationship between school violent crimes and safety policies and practices, two separate models for urban and rural schools were constructed. The values of goodness of fit were 1.785 in urban schools and 1.988 in rural schools, and both p-values for the omnibus tests were less than .001, suggesting good model fit of the data (Oyedepo & Etu, 2016).…”
Section: School Location-specific Negative Binomial Regression Model:...mentioning
confidence: 93%
See 1 more Smart Citation
“…To further test the effect of school location on the relationship between school violent crimes and safety policies and practices, two separate models for urban and rural schools were constructed. The values of goodness of fit were 1.785 in urban schools and 1.988 in rural schools, and both p-values for the omnibus tests were less than .001, suggesting good model fit of the data (Oyedepo & Etu, 2016).…”
Section: School Location-specific Negative Binomial Regression Model:...mentioning
confidence: 93%
“…Table 3 displays the results of negative binomial regression testing the effects of school characteristics, security measures, and school programs on incidences of violent crimes at schools within the whole sample. The value of goodness of fit was 1.852, and the p-value of the omnibus test was less than .001, indicating that the model fit the data well (Oyedepo & Etu, 2016). Ten of the independent predictors were significant in the model.…”
Section: Negative Binomial Regression Model: Total Sample (N = 2648)mentioning
confidence: 95%
“…Other aspects that influenced motorcycle ownership include the limitation of using a car, the leniency of using a motorcycle, the friction of living quality, and level of education. An investigation on factors affecting car ownership has been conducted in Akure, South West, Nigeria based on a multinomial logit model [16]. They stated that car ownership was influenced by the household income level and members, where an increase in income and family members by 50% was followed by an increase in the car ownership by 51% and 0,8%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For example [18], have applied Poisson regression to study the relationship between the travel times of the individuals and the number of motorized trips. [16] used Poisson and negative binomial regression to model car ownership in Nigeria. They found that car ownership was influenced by income and household members.…”
Section: Introductionmentioning
confidence: 99%
“…A α value of 0 or very close to it condenses the Negative Binomial Model to Poisson [9,[11][12][13].…”
mentioning
confidence: 99%